Eschatology in Hikayat Raja Jumjumah and Kunjarakarna - Safni Radhika; Munawar Holil (International Journal Labs, 2025)
The Hikayat Raja Jumjumah and Kunjarakarna manuscripts both contain stories concerning events related to death. This study aims to examine the eschatological concepts found in these Malay and Old Javanese texts. Both manuscripts are analyzed based on their transliterated versions. The data were collected through heuristic reading techniques. Subsequently, the data were compared and analyzed using textological methods to provide insight into the eschatological aspects of these two cross-cultural literary works. The objective of this research is to explore the eschatological concepts originating from two distinct manuscript traditions: Malay and Old Javanese. The findings reveal that in Kunjarakarna, eschatological elements are conveyed through the physical body, with no explicit depiction of death or the moment of dying. In contrast, Hikayat Raja Jumjumah employs the soul as the medium for its eschatological narrative, presenting a detailed account of death and the torments experienced.